Isolation and Identification of Mycoplasma mycoides Subspecies mycoides from the Ear Canal of Cattle in Plateau State, North-Central Nigeria. Issue 2 (2016) - Ankeli, Paul I.; Raji, Mashood A.; Kazeem, Haruna M.; Odugbo, Moses O.; Umaru, Nendir J.; O.Fagbamila, Idowu
No abstract available